2015
DOI: 10.1016/j.atherosclerosis.2015.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of IgG autoantibodies against the apolipoprotein B antigen p210 increases the risk of cardiovascular death after carotid endarterectomy

Abstract: Low levels of IgG autoantibodies against the apolipoprotein B antigen p210 increases the risk of cardiovascular death after carotid endarterectomy.Asciutto, Giuseppe; Dias, Nuno; Edsfeldt, Andreas; Alm, Ragnar; Nordin Fredrikson, Gunilla; Goncalves, Isabel; Nilsson, Jan Link to publication Citation for published version (APA): Asciutto, G., Dias, N., Edsfeldt, A., Alm, R., Nordin Fredrikson, G., Goncalves, I., & Nilsson, J. (2015). Low levels of IgG autoantibodies against the apolipoprotein B antigen p210 incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
3
9
1
2
Order By: Relevance
“…Asciutto et al reported recently that low levels of IgG autoantibodies against the native or MDA-modified apoB peptide p210 are associated with an increased risk of cardiovascular death in patients undergoing carotid endarterectomy [ 71 ]. The activation of macrophages by IgG-IC is determined by the balance between the triggering of activating ITAM-bearing FcγRs and the triggering of inhibitory ITIM-bearing FcγRIIB.…”
Section: Discussionmentioning
confidence: 99%
“…Asciutto et al reported recently that low levels of IgG autoantibodies against the native or MDA-modified apoB peptide p210 are associated with an increased risk of cardiovascular death in patients undergoing carotid endarterectomy [ 71 ]. The activation of macrophages by IgG-IC is determined by the balance between the triggering of activating ITAM-bearing FcγRs and the triggering of inhibitory ITIM-bearing FcγRIIB.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen peptide antigens (hAgs) derived from native human ApoB were designed based on the computational prediction of HLA-II restricted epitopes [ 32 ] and on the epitope information for human disease in the Immune Epitope Database ( http://www.iedb.org/ ). These 15 hAgs were all linear antigens with 25–30 amino acid residues that were applied to develop an ELISA in-house for detection of circulating anti-ApoB100 IgG levels based on the method described in our previous studies [ 44 , 45 ]. The sequences of these 15 antigens are given in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, some studies show a positive relationship of IgG autoantibodies titers with the development of atherosclerosis (124,147,148). Other authors, however, disagree with this direct relation; thus, Asciutto and coworkers reported that low levels of IgG anti-MDA-LDL correlates with high risk of postoperative death after carotid endarterectomy (149), whereas high levels of these antibodies are associated with decreased plaque inflammation (150). Moreover, studies performed in diabetic mice shows that treatments with anti-oxLDL IgG (151) or AGE-LDL immunization (152) protect against atherosclerosis, thereby suggesting a protective role for IgG autoantibodies.…”
Section: Modified Ldl As a Biomarker Of CV Risk In Dm And Metabolic Smentioning
confidence: 99%